Implementasi Nilai-Nilai Pendidikan Karakter dalam Surah Luqman Ayat 12-19: (Studi Living Al-Quran Pada Lembaga Dakwah Islam Indonesia di Cabai Rawit) - Tristiyani, Rizma Ayu; Fatah, Abdul (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Character education is very basic in the modern era. Especially character education for children, because children are the seeds that will grow and develop. The future of children will depend greatly on the character intake they receive at a young age. So it is very important to provide the right education at the early age of children's growth and development. One program that provides character intake for children is the Cabai Rawit program at the Indonesian Islamic Propagation Institute. Cabai Rawit is an educational effort carried out by LDII as a form of concern for children's character education. The program aims to shape children's character from an early age with religious moral values. The program is realized through various educational learning activities, so that children grow morally and naturally in character. This study aims to determine how the character education process is in the Cabai Rawit program at the Indonesian Islamic Propagation Institute, and how this education is in the view of the interpretation of the Qur'an, Surah Al Luqman verses 12-19.